Exaustão parental e uso de telas por crianças : estudo comparativo entre mães de crianças autistas e mães de crianças em desenvolvimento típico - Soares, Maria Gabriela Vicente (2025)
Parental exhaustion, particularly among mothers of children with autism spectrum disorder (ASD), has garnered increasing attention in psychology due to its significant impact on mental health and family dynamics. This dissertation aims to investigate the relationship between maternal parental exhaustion and children's screen time, comparing mothers of children with ASD to mothers of typically developing children. Parental exhaustion has been associated with substantial effects on parents’ mental health and the family environment, especially in contexts where caregiving demands are more intense, such as with children with ASD. This study explores this relationship, considering factors like maternal exhaustion and potential implications for managing children's screen time. The research included the development and validation of an instrument to measure parental exhaustion, as well as an examination of correlations between parental exhaustion and screen time management, comparing the two groups of mothers. Additionally, the study aimed to identify potential differences in sociodemographic variables such as family income, child age, marital status, and education level, and how these variables influence parental exhaustion and screen time. The central hypothesis suggested that mothers of children with ASD would exhibit higher levels of parental exhaustion, resulting in greater screen time usage among their children. The dissertation is organized into an introduction, a theoretical chapter on parental exhaustion and screen time, two empirical articles, and final considerations. The first article, focused on the development and validation of a scale to measure parental exhaustion, involved an exploratory factor analysis and three confirmatory factor analyses, demonstrating validity evidence for an instrument suitable for the Brazilian context. This study provided a reliable and valid measure of parental exhaustion with potential applications in various research and intervention contexts related to maternal well-being. The second article examined the relationship between parental exhaustion and screen time management. While contextual and sociodemographic variables differed between groups, no statistically significant relationship was found between parental exhaustion and screen time. However, distinct patterns emerged, particularly regarding the challenges faced by mothers of children with ASD in setting screen time limits and the association between mothers' education levels and their exhaustion levels. This study highlights the importance of understanding family dynamics, particularly in the context of ASD, and contributes to the literature on parenting. The findings provide insights into how sociodemographic factors and parental exhaustion influence parenting practices and child development. The research underscores the need for further studies on parental exhaustion, especially in specific contexts like ASD, and for the development of interventions to support families, improving quality of life and well-being for both parents and children. The validated instrument for measuring parental exhaustion represents a significant contribution to research in this field and has practical implications for studies and interventions aimed at parents' mental health.